Innovation in assessment: building student confidence in preparation for unfamiliar assessment methods - Spendlove, Z.; Best, R. (Mark Allen Healthcare, 2018)
Innovative assessment methods in which students are active participants promote deeper learning. A group debate and a webfolio were implemented as methods of assessment in the 2015 undergraduate midwifery curriculum, with the assessment tools being evaluated by students. Thematic analysis of the evaluations showed students enjoyed undertaking innovative methods of assessment, they developed confidence and engaged meaningfully with the content to be assessed. Students also commented they developed multiple skills required for future professional practice as a midwife. Thorough preparation of students to undertake an innovative method of assessment however is vital in fostering student confidence.